2022
DOI: 10.5334/cstp.511
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Citizen Science and Dissemination of Knowledge in Healthcare

Abstract: Citizen science goes by many names, especially when citizen science is applied to healthcare and biomedicine: There are patient researchers, patient-driven innovators, lead users, quantified self-trackers, and more. Citizen science in healthcare goes beyond data collection; citizen scientists themselves perform many stages of science and research all the way through to dissemination of their work. They may find themselves facing barriers similar to those facing traditional academic researchers in academic publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In their work, they identify a variety of ethical issues and considerations which are overdue for conversation and implementation (Wiggins & Wilbanks, 2019). Similar barriers to citizen science and patient-led research based in non-adapted ethical review procedures have been identified in other works as well (Lewis, 2022, Fiske et al, 2019. As such, the question of how to design and implement ethical oversight methodologies that can help facilitate health-related citizen sciencewhile serving and protecting non-institutional participantsremains an open and urgent question that should be given attention to help grow health-related citizen science.…”
Section: Factors For Growing Citizen Science In the Health Domainmentioning
confidence: 75%
See 1 more Smart Citation
“…In their work, they identify a variety of ethical issues and considerations which are overdue for conversation and implementation (Wiggins & Wilbanks, 2019). Similar barriers to citizen science and patient-led research based in non-adapted ethical review procedures have been identified in other works as well (Lewis, 2022, Fiske et al, 2019. As such, the question of how to design and implement ethical oversight methodologies that can help facilitate health-related citizen sciencewhile serving and protecting non-institutional participantsremains an open and urgent question that should be given attention to help grow health-related citizen science.…”
Section: Factors For Growing Citizen Science In the Health Domainmentioning
confidence: 75%
“…We see some evidence of this in our survey, as people with health conditions on average do rank access to literature higher than academic researchers (Figure 6). Beyond barriers to access in terms of reading the literature, and even though that some publishers are currently promoting the inclusion of patients as co-authors and also involved in the peer-review process in journals such as BMC Medicine or the Lancet (Boyce 2018), patients face an even higher barrier when it comes to trying to publish their own original research (Lewis 2022). This is reflected in the other condition for growth of citizen science practice in the health domain, 'citizen visibility'.…”
Section: Factors For Growing Citizen Science In the Health Domainmentioning
confidence: 99%
“…Planned strategies such as through news media, social media, policy briefs, one-on-one meetings, workshops, and seminars [ 7 ] are better suited to reach an audience that can create societal change, e.g., practitioners and policymakers [ 1 ]. Importantly, the use of traditional dissemination methods is linked to significant costs, including submission fees, article publishing charges (APCs), or open access (OA) charges [ 21 ]. Brownson and colleagues [ 10 ] plea for a change in how research is funded and how researchers are incentivized, requiring institutions to commit to dissemination for the long term.…”
Section: Discussionmentioning
confidence: 99%
“…These matrix representations are developed as follows. The formal mathematical graph representation of the network, as described in [25], is G(t) = {N(t), L(t), f (t)}, with time t, nodes N, links L, and mapping function f : N × N that connects node pairs for network topology. The proposed network model contains K = 6 nodes and M = 15 weighted links.…”
Section: Dynamic Network Model Describes the Temporal Patterns Of Emb...mentioning
confidence: 99%